Hunting for hides : deerskins, status, and cultural change in the protohistoric Appalachians - Lapham, Heather A. (Heather Alynn), 1969- (Book collections on Project MUSE., 2005)
Changes in Native American communities as they adapted to advancing Europeans. ℗¡ This volume investigates the use of deer, deerskins, and nonlocal goods in the period from A.D. 1400 to 1700 to gain a comprehensive understanding of historic-era cultural changes taking place within Native American communities in the southern Appalachian Highlands. In the 1600s, hunting deer to obtain hides for commercial trade evolved into a substantial economic enterprise for many Native Americans in the Middle Atlantic and Southeast.℗¡ An overseas market demand for animal hides and furs imported from the Americ.